Modern problems of management of enterprise financial assets and methods of their solutions. (Journal of Economic Research & Business Administration, 2015)
The article studied modern financial enterprise management problem assets, and possible ways to solve them today. The article also examines the management of financial assets.Which are based on a detailed analysis and enable us to determine financial stability and solvency of the company.The article investigates the optimization of projected cash flow and financial assets with different techniques and models.